Facework and gestures: a preliminary analysis of the communicative power of human performative non-verbal practices - Puppel, Joanna (Scripta Neophilologica Posnaniensia, 2018)
Facework and gestures: a preliminary analysis of the communicative power of human performative non-verbal practices